Managing higher education brands with an emerging brand architecture: the role of shared values and competing brand identities. (18th May 2020) - Spry, Louise; Foster, Carley; Pich, Christopher; Peart, Sheine
ABSTRACT: Corporate branding is a strategic issue for universities as the global higher education (HE) marketplace is becoming increasingly competitive and there is pressure to differentiate. Yet it is unclear how universities develop and manage brand strategies, and whether they draw upon any meaningful connections to the multiple stakeholders and sub-cultures engaged with a university's brand. Using qualitative data gathered from an education faculty within an established UK university, this study found the faculty and university had competing brand identities and images. A strong faculty brand emerged co-created through the shared teacher related values of staff and external partners. This study contributes to the brand strategy literature by applying branding concepts to the under-researched HE context and proposing a new, more nuanced brand architecture model not yet reported in the branding literature which more accurately reflects the management of sub and corporate HE brands.